Supplementation with long chain n-3 fatty acids during pregnancy, lactation, or infancy in relation to risk of asthma and atopic disease during childhood: a systematic review and meta-analysis of randomized controlled clinical trials - Linnea Bärebring; Bright I. Nwaru; Christel Lamberg-Allardt; Birna Thorisdottir; Alfons Ramel; Fredrik Söderlund; Erik Kristoffer Arnesen; Jutta Dierkes; Agneta Åkesson (Food & Nutrition Research, 2022)
Objective: To assess whether supplementation with long chain n-3 fatty acids during pregnancy, lactation, or infancy reduces the risk of developing asthma or atopic disease during childhood. Methods: Searches were performed in MEDLINE, Embase, Cochrane Central Register of Controlled Trials, and Scopus up to 2021-09-20, for randomized controlled trials (RCTs) that investigated the effect of supplemental long chain n-3 fatty acids during pregnancy, lactation, or infancy for the prevention of childhood asthma or allergy. Article selection, data extraction, and risk of bias assessment (Cochrane’s Risk of Bias 2.0) were independently conducted by two assessors. The evidence was synthesized qualitatively according to the criteria of the World Cancer Research Fund and meta-analyzed. Results: A total of nine RCTs met inclusion criteria; six were conducted during pregnancy, two during infancy, and one during both pregnancy and infancy. Meta-analysis showed that long chain n-3 fatty acid supplementation during pregnancy significantly reduced the risk of asthma/wheeze in the child (RR 0.62 [95% confidence interval 0.34–0.91], P = 0.005, I2 = 67.4%), but not other outcomes. Supplementation during lactation of infancy showed no effects on any outcome. The strength of evidence that long chain n-3 fatty acid supplementation during pregnancy reduces risk of asthma/wheeze in the offspring was considered limited – suggestive. No conclusion could be made for the effects of long chain n-3 fatty acid supplementation during pregnancy for other atopic diseases, or for supplementation during lactation or infancy for any outcome. Conclusion: The intake of long chain n-3 fatty acid supplements during pregnancy may reduce the risk of asthma and/or wheeze in the offspring, but the strength of evidence is low. There is inconclusive evidence for the effects of long chain n-3 fatty acid supplements during pregnancy for other outcomes, as well as for supplementation during lactation or infancy.